2010
DOI: 10.1080/08964289.2010.516783
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Family History of Breast Cancer and Health-Related Behavior

Abstract: This article explores the relationship between family history of breast cancer (FHBC) and health-related behavior and medical management, using a cross-sectional analysis of 685 women, based on self-report. The influence of FHBC on lifestyle (alcohol use, physical activity, weight and diet) and medical management decisions (screening for chronic diseases) was assessed using odds ratios (OR) and 95% confidence interval (CI). Adjustment for confounders was performed using unconditional logistic regression. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…17,23 In our study, women with an FMH of breast or ovarian cancer had health behaviors similar to women without an FMH of cancer. Other studies have found similar results, 24,25 although some studies have found more intense or higher levels of physical activity in women with a family history of breast cancer, [26][27][28] or greater practice of health behaviors was observed, as compared with the general population. 26 In some of these studies, data were drawn on women of higher education or socioeconomic status; 26,28 therefore, these findings may not be generalizable to other populations, including ours.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…17,23 In our study, women with an FMH of breast or ovarian cancer had health behaviors similar to women without an FMH of cancer. Other studies have found similar results, 24,25 although some studies have found more intense or higher levels of physical activity in women with a family history of breast cancer, [26][27][28] or greater practice of health behaviors was observed, as compared with the general population. 26 In some of these studies, data were drawn on women of higher education or socioeconomic status; 26,28 therefore, these findings may not be generalizable to other populations, including ours.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies have found similar results, 24,25 although some studies have found more intense or higher levels of physical activity in women with a family history of breast cancer, [26][27][28] or greater practice of health behaviors was observed, as compared with the general population. 26 In some of these studies, data were drawn on women of higher education or socioeconomic status; 26,28 therefore, these findings may not be generalizable to other populations, including ours. All health behavior models control for age, sex, race/ethnicity, household income, education, usual health-care provider, and marital status.…”
Section: Discussionmentioning
confidence: 61%
“…We excluded studies not conducted in the United States because important determinants of cancer screening such as healthcare coverage (8) vary by country. We excluded studies conducted in special populations (e.g., subjects with a family history of colon cancer) for which screening recommendations and practices may differ (9, 10) and thus, obscure the association between obesity and cancer screening. We did not require a specific measure of adiposity or study design.…”
Section: Methodsmentioning
confidence: 99%
“…However, our understanding of the potential for risk reduction for the majority of modifiable of risk factors in this high risk group remains unknown. Studies investigating women with a strong family history of breast cancer have shown that these women are no more likely to engage in healthy lifestyle habits than women in the general population [31,32] making lifestyle interventions a potentially important target. The Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) is currently examining the role of various genetic modifiers of cancer risk in BRCA mutation carriers.…”
Section: Introductionmentioning
confidence: 99%